Answer:
B: a = 1, b= 7, c = -2
Explanation:
Quadratic Formula
![x=(-b \pm √(b^2-4ac) )/(2a)\quad\textsf{when}\:ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/y55l7v1y4waybbqvew3ea4eoity9iv8y2l.png)
Given:
![x=(-7\pm√(57))/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/e9r98p5ejk0h4ot3qnetemtbwfq7htbipu.png)
Comparing the terms of the given x-value with those of the quadratic formula:
![(-b \pm √(b^2-4ac) )/(2a)=(-7\pm√(57))/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/mtaw0j9lbefg9wkn4oxmrpipb9d1dee2un.png)
Therefore:
Using the found values of a and b to solve for c:
![\implies b^2-4ac=57](https://img.qammunity.org/2023/formulas/mathematics/high-school/i4frvp28y54huq6zy00pn3u30m5covzpfr.png)
![\implies (7)^2-4(1)c=57](https://img.qammunity.org/2023/formulas/mathematics/high-school/z6h9p9dolkoac6iu6zt0f4omucfbud6z2v.png)
![\implies 49-4c=57](https://img.qammunity.org/2023/formulas/mathematics/high-school/85wpskuhz0nb8yl2zo4ewica3iins4iwa5.png)
![\implies -4c=57-49](https://img.qammunity.org/2023/formulas/mathematics/high-school/yi8mmytrndsfzqwzh6fdjkx5ng0vqggbdp.png)
![\implies -4c=8](https://img.qammunity.org/2023/formulas/mathematics/high-school/2pfjcghqyiy9y1ao304fihdaik989vkb4l.png)
![\implies c=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/mmwvsg0wh59u9c29gxgmb9avv4p8ykh19f.png)
In summary: a = 1, b = 7, c = -2
![\implies x^2+7x-2=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/x5p67rr9er1l18tyicnx9wodmy3mso5z23.png)
Therefore, option B is the correct solution.